2014
DOI: 10.1007/s12035-014-8717-6
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Mechanism of Neurogenesis by IGF-1 in Adult Mice

Abstract: Growth factors like insulin-like growth factor 1 (IGF-1) is reported to mediate neurogenesis in the subgranular zone (SGZ) and the subventricular zone (SVZ) of the adult mammalian brain, but its regulatory mechanism remains unclear. We generated transgenic mice overexpressing IGF-1 specifically in neural stem cells (NSCs) and assessed the effect of IGF-1 on neurogenesis in adult mice NSCs. Overexpression of IGF-1 could stimulate the expression of phospho-Akt and phospho-ERK1/2 while inducing proliferation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 46 publications
3
42
1
Order By: Relevance
“…The increase in the number of cycling cells detected in the Igf‐I KO mouse seems not to agree with previous data from studies into the action of exogenous IGF‐I. Indeed, IGF‐I stimulates the proliferation of embryonic NSCs and the overexpression or peripheral administration of IGF‐I enhances the number of proliferative cells in the postnatal/adult HP . By contrast and in line with our results, more proliferative cells in the postnatal SGZ of global Igf‐I KO mice were previously reported .…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The increase in the number of cycling cells detected in the Igf‐I KO mouse seems not to agree with previous data from studies into the action of exogenous IGF‐I. Indeed, IGF‐I stimulates the proliferation of embryonic NSCs and the overexpression or peripheral administration of IGF‐I enhances the number of proliferative cells in the postnatal/adult HP . By contrast and in line with our results, more proliferative cells in the postnatal SGZ of global Igf‐I KO mice were previously reported .…”
Section: Discussioncontrasting
confidence: 76%
“…Conditional deletion of the Igf‐I receptor gene ( Igf‐IR ) using the Nestin‐Cre strategy produces almost complete loss of the DG in mice . Moreover, exogenous IGF‐I promotes the proliferation of progenitor cells in the adult HP, both in culture and in vivo . This enhancement in cell proliferation is followed by the formation of granule neurons .…”
Section: Introductionmentioning
confidence: 99%
“…IGF-1 induces the proliferation and differentiation of NSCs via MEK/ERK pathway signaling and the PI3K/Akt pathway signaling in the SGZ and SVZ, respectively [Yuan et al, 2015]. …”
Section: Modulators Of Adult Neurogenesismentioning
confidence: 99%
“…12,13 A previous study has shown that IGF-1 promotes the proliferation of NSCs by interacting with the insulin-like growth factor 1 receptor (IGF-1R), which may activate the PI3K/AKT and MAP kinase pathways. 14 The IGF/IGFR system regulates the differentiation of neurons, astrocytes, and oligodendrocytes generated from NSCs in embryonic and adult brains. 15,16 In addition, IGF is also involved in the regulation of NSC migration, which is mediated by the activation of the PI3K pathway and by phosphorylation of the reelin signal transducer.…”
Section: Introductionmentioning
confidence: 99%